Mulheres pretas na ciência: cartografia existencial de pesquisadoras docentes de programas de pós-graduação em comunicação das universidades federais de Goiás e de Minas Gerais - Silva, Tuane Pacheco da (2023)
Black women suffer double discrimination due to their race and gender, and are therefore excluded from and neglected in various spaces, intellectual or otherwise. Historically, these women go through situations incomparable to those experienced by other women or other black people. It is in this sense that it is necessary to address the specific reality of these women. The purpose of this research was to raise this issue in the academic-scientific field. The research aligns with studies on science and intersectionality. Its objective was to map the existential territories of black women teaching postgraduate programs in communication at the Federal University of Goiás (UFG) and the Federal University of Minas Gerais (UFMG): who are these women; what are the paths of their educational training; how they constituted themselves as black women-academic subjects; How do they perceive the issue of race and gender in science and in their academic daily life? How they inhabit the academic-scientific territory; How do markers of race and gender permeate their ways of existing as professors and researchers working in the university environment? The aim was to highlight how gender and race markers are present in the ways of inhabiting the academic-scientific territory of black women and in the construction of their life and professional paths in a traditional way of doing Science. These questions were answered from the perspectives of the women themselves. To this end, in methodological terms, existential cartography was used, which included conducting in-depth interviews with black professors from the postgraduate communication programs at UFG and UFMG. Three teachers were interviewed, two (in total of 3) from UFG and one from UFMG. Thus, the research makes it possible to give visibility to the academic-scientific work of black women researchers, in order to contribute to the decolonization of the academic scientific environment, making it inclusive and open to black women. It is concluded that the three women interviewed build their academic-scientific territories with great effort and dedication, but that they feel the weight of racism in their trajectories. They see themselves as being unfairly treated by the system that surrounds them and which often prevents them from achieving more. They hope that universities are pluri-epistemic and have equal opportunities for everyone, a space with resources to help students, and in which the showcase of knowledge and greater interaction between researchers is applied. Therefore, the results indicate that the academic environment is racist and androcentric and that there is an urgent need to change this scenario so that science is equitable.